Penerapan Management Bandwith Dengan Metode Queue Tree Berbasis Mikrotik Untuk Mempermudah Proses Pembelajaran - Budi Wibowo; Andrie Yuswanto (Sultan Publisher, 2023)
Management of bandwidth by using a proxy method of queue tree serves to implement more complex functions within the bandwidth limit on the proxy where the use of its mark packet has better functions. Used to limit one direction only connection either download or upload with proxy, administrators facilitated in setting bandwidth evenly, determine the bandwidth limiter, and a set of wireless users. Administrators can monitor and control the user-users are connected to the internet hotspot network by managing and sharing of bandwidth as needed to optimize existing bandwidth availability, and be able to monitor users (user). Mikrotik according to the author is a cheap solution, but can be optimized as a network device that has features that can help network administrators in performing their duties.